Multiproduct supply chain - Strategic planning and forecasting - Zamora, Jose F. Roig; Forradellas, Raymundo Q.; Camargo, Mauricio (Brazilian Journal of Operations & Production Management, 2010)
The relation among the actor’s of the Supply Chain defi nes its main characteristics, and therefore the Distribution and Manufacturing Strategy that the actors must follow in order to fulfi ll the Service Equation. In a Multiproduct Supply Chain, the different Negotiating Force of the different actors will truly infl uence in the fi nal design on the Chain Confi guration. Depending on which actor has more power, the Supply Chain must react to different supply policies. Forecasting Tools are presented as an option to predict the product Distribution and Manufacturing needs and as a way to counterbalance the different negotiating force among actors.